The Effect of Price, Customer Reviews, and Online Merchandising on Customer Loyalty with Purchase Intention as an Intervening Variable at Nusantara Medika Jaya Store in Samarinda - Eka Yudhyani; Aliyah Aghitsni; Ivana Barus; Titin Ruliana; Sunarto Sunarto (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to analyze the influence of price, online customer reviews, and online merchandising on customer loyalty, with purchase intention as an intervening variable at the Nusantara Medika Jaya Store in Samarinda on the Shopee platform. The population in this study consists of all consumers who have visited or transacted at the Nusantara Medika Jaya Store via Shopee within the last six months. The sampling technique employed was non-probability sampling with a purposive sampling approach, resulting in 211 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results of the study indicate that out of the ten hypotheses tested, four were accepted and six were rejected. The main findings show that online merchandising has a positive and significant effect on purchase intention, and purchase intention has a positive and significant effect on customer loyalty. Furthermore, purchase intention is proven to mediate the influence of online merchandising on customer loyalty. Price was found to have a positive and significant direct effect on customer loyalty but did not significantly influence purchase intention. On the other hand, online customer reviews were not proven to have a significant influence on either purchase intention or customer loyalty within this research model. These results confirm that online merchandising is the primary driver of purchase intention, while price serves as a direct determining factor in building long-term customer loyalty at the Nusantara Medika Jaya Store in Samarinda.